Micro‐ and Nano‐Devices for Studying Subcellular Biology. Issue 3 (20th December 2020) - Siedlik, Michael J.; Yang, Zijian; Kadam, Parnika S.; Eberwine, James; Issadore, David
Abstract: Cells are complex machines whose behaviors arise from their internal collection of dynamically interacting organelles, supramolecular complexes, and cytoplasmic chemicals. The current understanding of the nature by which subcellular biology produces cell‐level behaviors is limited by the technological hurdle of measuring the large number (>10 3 ) of small‐sized (<1 μm) heterogeneous organelles and subcellular structures found within each cell. In this review, the emergence of a suite of micro‐ and nano‐technologies for studying intracellular biology on the scale of organelles is described. Devices that use microfluidic and microelectronic components for 1) extracting and isolating subcellular structures from cells and lysate; 2) analyzing the physiology of individual organelles; and 3) recreating subcellular assembly and functions in vitro, are described. The authors envision that the continued development of single organelle technologies and analyses will serve as a foundation for organelle systems biology and will allow new insight into fundamental and clinically relevant biological questions. Abstract : Next generation technologies capable of analyzing individual organelles are required to advance the understanding of how subcellular biology produces cell‐level behaviors. This review describes emerging nanofluidic, microfluidic, and microelectronic approaches that offer the potential to overcome the technological hurdle of measuring large numbers of dynamic, microscale biological structures and thus provide insight into fundamental and clinically relevant biological questions.